Kontribusi Khalifah Mochammad Ya’qub bin Muhamad Atim Dalam Thoriqoh Shiddiqiyyah di Palembang (1970 – 2023 M) - Mutiara Nursafitri; Otoman (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
This research discusses thoriqoh Shiddiqiyyah in Palembang. The arrival of the Shiddiqiyyah thoriqoh in Palembang in 1970 AD brought by the caliph Mochammad Ya'qub bin Muhamad Atim. Caliph Mochammad Ya'qub bin Muhamad Atim was one of the students who was given the mandate to broadcast the teachings of Thoriqoh Shiddiqiyyah precisely in Palembang. The teachings are conveyed through several methods such as the da'wah method, teaching Shiddiqiyyah teachings to the community, collective dhikr (Kautsaran), and with programs contained in Shiddiqiyyah, such as National Compensation, Construction of Livable Thankful Houses (commemoration of Indonesian National Independence and Youth Pledge Day) and others. other. Its followers have increased, with this increase in followers it can also be seen that the development of thoriqoh Shiddiqiyyah in Palembang is increasing, visible and known to the public. Caliph Mochammad Ya'qub bin Muhamad Atim arrived in Palembang alone at a young age at that time, there were no friends or students from other thoriqoh Shiddiqiyyah. At that time he lived in the Aryodilla area. With existing programs, you can increase followers of thoriqoh Shiddiqiyyah in Palembang. This research aims to determine the entry and development of thoriqoh Shiddiqiyyah and the contribution of the caliph Mochammad Ya'qub bin Muhamad Atim. This research is qualitative research that uses historical research methods utilizing a sociological approach. This research uses historical theory. Data collection techniques were obtained through a process of observation, interviews, documentation and literature study. Data sources were obtained through direct observation, interviews and documentation by the administrators and followers of Thoriqoh Shiddiqiyyah. and use books, journals or archives that are appropriate to the research.